Potential effects of samsum ant, Brachyponera sennaarensis, venom on TNF-α/NF-κB mediated inflammation in CCL4-toxicity in vivo. Issue 1 (December 2016) - Al-Tamimi, Jameel; Alhazza, Ibrahim; Al-Khalifa, Mohamed; Metwalli, Ali; Rady, Ahmed; Ebaid, Hossam
Abstract Background Ant venom shows antimicrobial, anti-parasitic and anti-inflammatory activities, both in vitro and in vivo. Our recent studies have confirmed the role of samsum ant venom (SAV) as a powerful antioxidant. This study aimed to investigate whether SAV as a potential treatment for CCl4-induced acute liver toxicity in an animal (rat) model. Methods Thirty-two rats were assigned into four groups; the first one served as the control. The second group received a single dose of 1 ml/kg CCl4 in a 1:1 ratio with olive oil through an intraperitoneal injection. The third group received a single dose of 1 ml/kg CCl4 and then treated with SAV at a dose of 100 μg SAV twice a week for three weeks. The fourth group received a dose of 100 μg SAV only twice a week for three weeks. ELISA, RT-PCR and histopathological examinations were applied. Results Results showed that antioxidant enzymes were significantly reduced in the diseased animals. SAV was found to significantly restore the oxidative stability in diseased animals. ELISA estimation and RT-PCR analysis also showed significant upregulation of both nuclear factor (κB) NF-κB and inhibitor (κB) IκB, respectively, in the diseased animals compared to the normal ones. The expression of tumour necrosis factor alpha (TNF-α) and pro-apoptotic receptor (Fas) were also significantly up-regulated in the diseased rats. Interestingly, SAV was found to significantly restore NF-κB, IκB and TNF-α in the diseased rats to the normal values. As a result, liver enzymes, serum proteins and lipid concentrations were significantly improved by SAV in CCl4-animals in comparison with the control ones. Moreover, SAV obviously improved the hepatic tissues of the same group was. Conclusion SAV treatment restores the normal biochemical and oxidative stability by improving the TNF-α/NF-κB mediated inflammation in CCL4-treated rats.